Aplicabilidade do pensamento enxuto e práticas sustentáveis na construção civil: estudo de caso em uma construtora alagoana - Gutierrez, Bárbara Coelho Medeiros (2020)
Faced with the phenomenon of globalization and scarcity of resources, organizations seek to innovate and improve their techniques, without losing the quality of services, adopting mechanisms to reduce or even eliminate expenses and waste. In this scenario, the study of lean thinking, idealized in 1988, initially by Ohno, proves to be an effective method that can be applied today, not only in production but also in civil construction, being thus an advantageous and revolutionary alternative . This work describes "Lean Construction#, through the approach of its principles and tools, verifying the application of these elements by the construction companies. This work aims to carry out a study based on the ideologies of "Lean# thinking, in order to discuss and present strategies used in civil construction to organize production, and consequently, to reduce company expenses. The research strategy was a case study based on bibliographic research in line with the data provided by the construction company from Alagoas. Data analysis was carried out by observing the previous items, the result of which was a reduction in water consumption at the construction site between 30% and 40%, by reusing it, in addition to reducing waste from construction. The conclusion of this study lies in its strategic importance, as it contributes to more companies adopting "Lean Construction#, thus increasing their productivity and their environmental responsibility.